Deconstructing Capitalist Accounting: Integrating The Liberation Theology Paradigm In Islamic Accounting - Satiadharmanto, Deddi Fasmadhy; Nugraha, Muh. Qudrat; Muhtadin, Imam (Abadi Institute, 2024)
This study aims to deconstruct the concept of accounting, which is dominated by capitalism, through the integration of the liberation theology paradigm in Islamic accounting. Using a qualitative approach and literature review method, this research explores how the liberation theology paradigm can provide a more just and humanistic ideological foundation in accounting practices. The study involves a critical analysis of literature related to Western epistemology in accounting, as well as ontological, epistemological, and axiological approaches from an Islamic perspective. The findings show that the liberation theology paradigm in Islamic accounting can offer a more ethical and just alternative compared to conventional accounting, which is often driven by capitalist interests. This research concludes that the integration of liberation theology in Islamic accounting not only expands the scope of accounting but also strengthens its role as a tool for social liberation. The results indicate that the Islamic metaphysics approach successfully deconstructs the dominance of Western epistemology in accounting by rejecting the concept of binary oppositions often used to separate economic and spiritual aspects. Through the liberation theology paradigm, Islamic accounting is presented as a more just ideological framework, where God is placed at the center of the ontology of accounting, emphasizing the importance of integrating spiritual values into every economic decision. This approach not only critiques but also offers an alternative by integrating ontological, epistemological, and axiological aspects in accounting, creating a more holistic and ethical concept, and reaffirming accounting’s role as a tool for social liberation based on justice and Islamic values.